2013
DOI: 10.1293/tox.2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Proper Heat Shock Pretreatment Reduces Acute Liver Injury Induced by Carbon Tetrachloride and Accelerates Liver Repair in Mice

Abstract: Whether proper heat shock preconditioning can reduce liver injury and accelerate liver repair after acute liver injury is worth study. So mice received heat shock preconditioning at 40°C for 10 minutes (min), 20 min or 30 min and recovered at room temperature for 8 hours (h) under normal feeding conditions. Then acute liver injury was induced in the heat shock-pretreated mice and unheated control mice by intraperitoneal (i.p.) injection of carbon tetrachloride (CCl4). Hematoxylin and eosin (H&E) staining, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The widely recognized cytoprotective heat shock protein inducing hydroxylamine derivative, bimoclomol, also induced adaptive hormetic responses in multiple systems involving a spectrum of neuropathologies [ 142 ]. Similar hormetic patterns are very general, extending from plants [ 143 , 144 ] to invertebrates [ 145 147 ] and to mammals [ 148 151 ] affecting multiple indices of health and disease with a wide range of inducing agents.…”
Section: Cellular Stress Response and The Vitagene Systemmentioning
confidence: 89%
“…The widely recognized cytoprotective heat shock protein inducing hydroxylamine derivative, bimoclomol, also induced adaptive hormetic responses in multiple systems involving a spectrum of neuropathologies [ 142 ]. Similar hormetic patterns are very general, extending from plants [ 143 , 144 ] to invertebrates [ 145 147 ] and to mammals [ 148 151 ] affecting multiple indices of health and disease with a wide range of inducing agents.…”
Section: Cellular Stress Response and The Vitagene Systemmentioning
confidence: 89%
“…Western Blot Analysis. Protein isolation and immunoblotting procedures were performed as previously described (Li et al, 2013;Liu et al, 2013). Primary antibodies for immunoblotting included anti-GFAP (1:1000; Proteintech), anti-Iba1 (1:500; Abcam), anti-PPARg (1:500; Abcam), and anti-BACE1 (1:1000; Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Hsp70 is effective for the survival of cells and tissues by combining with hydrophobic regions in unfolded proteins in an adenosine triphosphate (ATP)-dependent manner to stabilize the unfolded state and then help proteins recover into a folded state. Li et al discovered that Hsp70 overexpression by heat-shock pretreatment can reduce the liver injury induced by carbon tetrachloride and accelerate liver repair in rats, and that these phenomena may be related to the anti-oxidative properties of Hsp70 (23) . Research has also shown that inhibition of Hsp70 expression by micro-injection of monoclonal antibodies against Hsp70 can weaken the survival and tolerance of fibroblasts during HS in vitro (24).…”
Section: Introductionmentioning
confidence: 99%